2008
DOI: 10.1124/dmd.108.023291
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Quetiapine by CYP3A4 and CYP3A5 in Presence or Absence of Cytochrome B5

Abstract: ABSTRACT:The antipsychotic drug quetiapine is extensively metabolized by CYP3A4, but little is known about the possible influence of the polymorphic enzyme CYP3A5. This in vitro study investigated the relative importance of CYP3A4 and CYP3A5 in the metabolism of quetiapine and compared the metabolic pattern by the two enzymes, in the presence or absence of cytochrome b 5 . Intrinsic clearance (CL int ) of quetiapine was determined by the substrate depletion approach in CYP3A4 and CYP3A5 insect cell microsomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Thus, the calculated CL int of N-desalkylquetiapine by CYP3A4 in the present study could potentially have been higher in microsomes coexpressed with cytochrome b 5 . However, the effect of cytochrome b 5 on CYP3A4 activity is substrate-specific (Yamaori et al, 2003), and we have previously shown that the in vitro metabolism of quetiapine was actually lower in recombinant CYP3A4 coexpressed with cytochrome b 5 (Bakken et al, 2009). The CL int value for CYP3A4-mediated metabolism is also more uncertain compared with CYP2D6, because the substrate loss in CYP3A4 microsomes was less than recommended (Jones and Houston, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the calculated CL int of N-desalkylquetiapine by CYP3A4 in the present study could potentially have been higher in microsomes coexpressed with cytochrome b 5 . However, the effect of cytochrome b 5 on CYP3A4 activity is substrate-specific (Yamaori et al, 2003), and we have previously shown that the in vitro metabolism of quetiapine was actually lower in recombinant CYP3A4 coexpressed with cytochrome b 5 (Bakken et al, 2009). The CL int value for CYP3A4-mediated metabolism is also more uncertain compared with CYP2D6, because the substrate loss in CYP3A4 microsomes was less than recommended (Jones and Houston, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…CYP3A is the main enzyme involved in the metabolism of quetiapine, responsible for the sulfoxidation, N-and O-dealkylation, and partially the 7-hydroxylation (Grimm et al, 1997;Bakken et al, 2009). The 7-hydroxy pathway is also catalyzed by CYP2D6 (Grimm et al, 2006), but this enzyme is of minor importance for the overall clearance of quetiapine (Hasselstrøm and Linnet, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…34) The V max /K m of quetiapine with cytochrome b 5 was less than 35% that of CYP3A4, and V max /K m for CYP3A4 without cytochrome b 5 was 3 times that of CYP3A4 with coexpressed cytochrome b 5 , whereas for CYP3A5, V max /K m was similar for both microsomal preparations. 66) Further detailed studies on the contribution of cytochrome b 5 are required in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For these 73 (Table 3). [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73] The mean (± S.D.) and median CYP3A5/CYP3A4 ratios of the metabolic activities in these 47 reactions were 0.69 ± 1.23 and 0.28, respectively.…”
Section: Metabolic Activity Of Cyp3a4 and Cyp3a5mentioning
confidence: 99%
“…Therefore, many in vitro studies relied on recombinant CYP3A4 as screening tool to evaluate potential drug-drug interactions (DDIs) in vivo. For this purpose, catalytically active recombinant human CYP3A4 isoform has been successfully expressed in E. coli [12], yeast [13], mammalian cells [14,15] and insect cells [16]. Meanwhile, different techniques have also been employed to enhance the enzymatic activity of recombinant CYP3A4, like co-expression and protein fusion [17][18][19].…”
Section: Introductionmentioning
confidence: 99%